The Role of Telenursing in Increasing Knowledge and Physical Activity of Breast Cancer Patients - Maulidta Karunianingtyas Wirawati; Tri Sakti Widyaningsih (GLOBAL HEALTH SCIENCE GROUP, 2022)
ancer is one of the leading causes of death worldwide. One type of Cancer which highly impact woman is breast cancer. Nowadays chemotherapy becomes the most advance therapy for cancer although it has a real impact in decreasing physical and psychological conditions of the patient. In order to improve their physical and psychological condition, mentoring or assistances is needed. In current developments, mentoring can be done directly or indirectly including by utilizing technology as known as Telenursing. This Quasi Experimental study was used a pretest-posttest with control group design. All breast cancer patients who were in a home stay around Semarang were involved in this study. There is a significant difference in knowledge before intervention and after intervention (p-value = 0.000). It can be concluded that mentoring by utilizing Telenursing has impact in increasing the knowledge of breast cancer patients about physical activity. There is a significant difference in the behavior before and after the intervention (p-value = 0.002).